Does endometriosis affect professional life? A matched case-control study in Switzerland, Germany and Austria. Issue 1 (9th January 2019) - Sperschneider, Marita Lina; Hengartner, Michael P; Kohl-Schwartz, Alexandra; Geraedts, Kirsten; Rauchfuss, Martina; Woelfler, Monika Martina; Haeberlin, Felix; von Orelli, Stephanie; Eberhard, Markus; Maurer, Franziska; Imthurn, Bruno; Imesch, Patrick; et al.
Abstract : Objectives: Endometriosis is a gynaecological disease most commonly causing severe and chronic pelvic pain as well as an impaired quality of life. The aim of this study was to investigate if and how endometriosis affects choices regarding professional life as well as the quality of daily working life. Design, setting and participants: In the context of a multicentre case–control study, we collected data from 505 women with surgically/histologically confirmed diagnosis of endometriosis and 505 matched controls. Study participants were recruited prospectively in hospitals and doctors' practices in Switzerland, Germany and Austria. Using a detailed questionnaire, the study investigated work–life and career choices of study participants. Main outcome measures: Associations between endometriosis/disease symptoms and limitations in career development as well as ability to work. Results: Women with endometriosis were less often able to work in their desired profession than women from the control group (adjusted OR=1.84, 95% CI: 1.15 to 2.94, R 2 =0.029, p=0.001) and they had to take health-related limitations into consideration in their career decisions to a significantly higher degree than women in the control group (OR=4.79, 95% CI: 2.30 to 9.96, R 2 =0.063, p<0.001). Among women with endometriosis, chronic pain was significantly associated with increased sick leave (OR=3.52, 95% CI: 2.02 to 6.13, R 2 =0.072, p<0.001) as well as with loss of productivity at work (OR=3.08, 95% CI: 2.11 to 4.50, R 2 =0.087, p<0.001). Conclusions: Endometriosis is associated with impairment of professional life, in particular with regard to career choices. Further research to develop strategies to support endometriosis-affected women in realising professional opportunities is recommended. Trial registration number: NCT02511626 ; Pre-results.